A102 THIOPURINE METABOLITE LEVEL MONITORING LEADS TO INDIVIDUALIZED AND OPTIMIZED THIOPURINE THERAPY IN ADULT INFLAMMATORY BOWEL DISEASE (IBD). (1st March 2018) - Zhu, J; Abraldes, J; Dieleman, L A; Huang, V; Kroeker, K I; Peerani, F; Wong, K; LeGatt, D; Fedorak, R; Halloran, B P
Abstract: Background: The thiopurine drugs (6-MP, azathioprine (AZA)) are purine anti-metabolites commonly used in IBD. About 55% of active IBD fail to respond to thiopurine weight based dosing. Studies suggest 6-thioguanine (6-TG) and 6-methylmercaptopurine (6-MMP) levels are better therapeutic targets than weight-based regimens. The therapeutic range of 6-TG is 400–750*. 6-TG levels >750*, 6-MMP levels >6600* increase risk of bone marrow, hepatic toxicity respectively. Xanthine oxidase inhibitor allopurinol (ALL) can decrease the shunting to 6-MMP and increase 6-TG levels in "shunters" (6-MMP/6-TG ratios >20). Aims: To assess thiopurine metabolite levels in adult IBD patients, physician response to levels, how they altered therapy and patient outcomes. Methods: Metabolite levels were obtained retrospectively from a chart review of 159 adult IBD patients between 2014 and 2015. All had levels measured for non-response or toxicity. Clinical outcomes were examined. Steady state metabolite levels were analyzed using the Dervieux-Boulieu method. Results: Sub-therapeutic (subT) clinical response was the main indication for assessing levels (69.2%). Mean 6-TG and 6-MMP levels were 443.4*, 3690.5* respectively. SubT 6-TG and supra-target 6-MMP levels occurred in 95 (60%), 27 (17%) patients. Mean 6-MMP/6-TG ratio was 10.9 (95% CI 8.8–13.0). There were 25 shunters with mean ratio 35.1 (range 21.2–68.1). Overall physician responses to abnormal levels were dose alternation or initiating new therapy (89%), and to diagnosis of shunting was dose reduction with initiation of ALL (76% (19/25)). Highest concordance was seen in subT 6-TG levels and sub-clinical response (59%). AZA dose escalation did not lead to incremental change in 6-TG level; 6-MMP level was nonlinearly increased by higher AZA dose (Figure 1). Highest 6-TG levels (586.6*) were seen in AZA+5-ASA+anti-TNFα group (95% CI 429.8–734.4*, AZA 137.5mg) compared to thiopurine monotherapy group (474.1*, 95% CI 361.7–586.6*, AZA 160.7mg). Lowest 6-TG level 392.4*(95% CI 303.5–481.3*, AZA 141.2mg) was seen in AZA+anti-TNFα group (NS ANOVA p= 0.32). There was no difference in AZA dose in these three groups (p=0.19). AZA dose was lowest in AZA+ALL group, and achieved comparable 6-TG levels (AZA 71.4mg, p<0.0002, 6-TG 453.3* p=0.66). In 5 patients, metabolite levels were re-measured; there were reduction of 6-MMP and increased 6-TG levels post ALL use and none developed side effects (Table 1). Conclusions: This data suggests that weight based dosing is a suboptimal way to achieve therapeutic levels of 6-TG. The addition of ALL may be a safe alternative for those who do not response to standard dose escalation. The optimal interval of serial metabolite monitoring remains to be determined. *pmol/8x10 8 RBC Funding Agencies: None